Retained multiple contact lenses in a vulnerable dementia patient - Rohit SHARMA; Zuhair SHARIF (Journal of Health and Social Sciences)
We report a case of an 85-year-old female nursing home resident with a background of dementia, who pre- sented to the eye casualty clinic complaining of an 8-month history of a painful red eye and reduced vision. Treated ‘on and off ’ by various doctors and healthcare professionals with antibiotic drops for eight months with no improvement. Eversion of the upper eye lid revealed an infected foreign body which turned out to be multiple contact lenses stacked on top of each other. Further history taking from her son suggested that the contact lenses were possibly left in for 3 years or longer when he noticed carers stopped replacing them at the care home. Patients with dementia are vulnerable adults and are at an increased risk of intentional or unintentional abuse and neglect. Careful care and attention should be given when taking a history and examining a patient with dementia. The case also highlights the importance of upper lid eversion as part of a thorough eye examination especially in patients who might have difficulty providing a history of a mi- splaced contact lens. This is the first such case to the best of our knowledge of retained contact lenses in a dementia patient. Patients with dementia should be advised against contact lens wear. Also the need for ca- reful mandatory documentation in the clinical notes and communications to the general practitioner or care home about the insertion and removal of contact lenses with dates and name of professional perfoming this.